EXPLORING CONTRIBUTION AND CHALLENGES TOWARDS SOCIOECONOMIC DEVELOPMENT IN BANGLADESH: THE CASE OF READY-MADE GARMENTS INDUSTRY - Li, Cheng Lung; Khandoker, Anowar Hossain; Li, Alvin (International Journal of Application on Economics and Business, 2025)
This study aims to explore stakeholders' perspectives on the contributions and challenges of the Ready-Made Garments (RMG) sector which lead to socioeconomic development in Bangladesh. This research employs a qualitative approach, utilizing interviews, surveys, and focus group discussions to collect data. Participants include factory owners, government officials, industry experts, workers' representatives, and economists. The study finds that the RMG sector significantly contributes to poverty alleviation by providing employment opportunities, particularly for women and rural migrants. Employment in the sector enhances household incomes and promotes socioeconomic mobility. Additionally, RMG exports constitute a substantial portion of Bangladesh's total export earnings, supporting macroeconomic stability and economic development. However, the sector faces significant challenges, including labor rights issues, poor working conditions, and intense global competition. These challenges hinder the sector's sustainability and require targeted interventions to improve labor standards and competitive positioning. Stakeholders emphasize the need for policy reforms, technological advancements, and capacity-building initiatives to address these challenges and enhance the sector's sustainable growth.